MEMAKNAI SELFHEALING DENGAN DZIKIR - Niskaromah Niskaromah (Journal of Innovation Research and Knowledge, 2023)
Globalization brings changes to the value system of life running fast. Society is also faced with increasingly diverse problems as a result of modernization and technological advances. Personal inability to achieve oneself according to environmental demands can lead to instability within a person, and stress becomes something that cannot be avoided. The many pressures of life bring awareness to the importance of mental health. Self-healing (healing without using drugs) is a very popular alternative. Some of the methods applied in self-healing include; Forgiveness, Gratitude, SelfCompassion, Mindfulness, Positive self-talk, SelfAcceptance, and relaxation. The method applied in self-healing does not include dhikr, which actually has a very large side effect in bringing peace to one's soul. This study uses a qualitative approach, which is presented descriptively from the point of view of religious values. The data presented in this study is in the form of writing and not in the form of numbers. Primary data was obtained directly from the book SelfHealing is Knowing Your Own Self by Diana Rahmasari and Al-Wabîl al-Shayyib wa Râfi' al-Kalim al-Thayyib by Ibnu Qayyim al-Jauziyyah. Secondary data is obtained from books, journals, seminar papers and other accurate data related to the research object. Through descriptive analysis, a comparison between the two methods is presented to obtain a systematic, factual, and accurate description of the phenomenon under study. The results of the study show that both self-healing and dhikr methods can be used as a means to heal inner wounds but on a different basis. The method used in carrying out self-healing is included in the realm of applying easy morals or commendable morals to oneself, others and Allah Swt as the Creator with the aim of getting inner peace over the upheaval that has occurred. Unlike the self-healing method, the main goal of dhikr is taqarrub to Allah Swt. Intense dhikr will create a connection between a creature and his God. This connection brings a sense of serenity that dispels all worries because of its closeness to the Creator.